Corporate lobbying, CEO political ideology and firm performance - Unsal, Omer; Hassan, M. Kabir; Zirek, Duygu (Journal of Corporate Finance, 2016)
In this paper, we investigate the influence of CEO political orientation on corporate lobbying efforts. Specifically, we study whether CEO political ideology, in terms of manager-level campaign donations, determines the choice and amount of firm lobbying involvement and the impact of lobbying on firm value. We find a generous engagement in lobbying efforts by firms with Republican leaning-managers, which lobby a larger number of bills and have higher lobbying expenditures. However, the cost of lobbying offsets the benefit for firms with Republican CEOs. We report higher agency costs of free cash flow, lower Tobin's Q, and smaller increases in buy and hold abnormal returns following lobbying activities for firms with Republican managers, compared to Democratic and Apolitical rivals. Overall, our results suggest that the effects of lobbying on firm performance vary across firms with different managerial political orientations.